Efficacité d’utilisation du jeu Drops pour enrichir le vocabulaire français des élèves de SMAN 7 Binjai - Erra Fazira Fay Siregar; Abdul Ghofur (Didacticofrancia Journal Didactique du FLE, 2026)
This research aims to determine the effectiveness of using the playful application Drops to enrich students in class XI 2/Soshum’s French vocabulary in class at SMAN 7 Binjai High School. The research uses a quantitative, quasi-experimental design, namely the One-Group Pretest-Posttest Design. Data collection instruments include a pre-test, post-test, observations, and questionnaires. 30 students from class XI 2/Soshum SMAN 7 Binjai for the 2024/2025 school year were selected using a purposive sampling method for the research topics. The results showed that after using the Drops game app, students’ average grades increased significantly. The average score before the test is 46, and after the test, it is 84.6. To improve mastery of vocabulary in the material “Se Présent: Salutation, les Chiffres, la Profession et le Sport, la Nationalité”, the use of the Drops app is rated “very effective” based on t-test results and N-Gain calculations. Therefore, it can be concluded that the Drops game app is an effective tool to help students learn more French vocabulary.